Auditor independence and competence’s impact on quality audit results - Heru Satria Rukmana; Towaf Totok Irawan; Retno Martanti Endah Lestari; Siti Maimunah (Technium Business and Management, 2025)
The purpose of this study is to investigate how audit quality is affected by the personal features, experience, and independence of the auditor. Gaps in prior studies and the significance of these elements in affecting audit quality form the basis of this issue’s background. The main goal of this study is to present actual data regarding the correlation between audit quality and the personal characteristics, experience, and independence of auditors. Quantitative research using a descriptive and verification approach is the methodology employed. The research sample for this study consists of auditors from Public Accounting Firms (KAP) in Jakarta and the neighboring areas. Purposive sampling is the method used, and a minimum sample size of 110 auditors is required. Data were collected through an online questionnaire distributed via Google Forms and measured using a Likert scale. Data analysis was conducted using Structural Equation Modeling (SEM) with SmartPLS 4 software. The results indicate that the variables of auditor personal traits, auditor experience, and auditor independence positively influence audit quality. These findings contribute significantly to both academics and practitioners by enriching the literature and can serve as a reference for the advancement of economic science, particularly in the field of auditing.